Ash vs Evil Dead. the complete collection [videorecording (Blu-Ray)] - Campbell, Bruce; Raimi, Sam; Raimi, Sam; Bassett, Michael J; Campbell, Bruce, 1958-; Santiago, Ray, 1984-; Lawless, Lucy, 1968- (Lionsgate, 2018)
When Ash accidentally unleashes a plague of Deadites, he must find a way to destroy them.